Crossing the line: unprotected and unseen; vasa previa and the perils of fetal vessel rupture - Padhy, Sanghamitra; Kumar, Ashish; E. Amara, Umm; Nashrah, Umme; Shaikh, Nissar; Ummunnisa, Firdos (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Vasa previa is a rare but life-threatening obstetric condition in which unprotected fetal vessels traverse the fetal membranes near the cervical OS, predisposing them to rupture during labor or membrane rupture. We present the case of a 39-year-old gravida 3 para 2 woman at 39 weeks gestation with a history of assisted reproductive technology conception and a low-lying placenta. Following induction of labor and artificial rupture of membranes, she developed sudden vaginal bleeding with fetal bradycardia. Emergency cesarean section was performed under general anesthesia. The patient experienced massive peripartum hemorrhage requiring transfusion of multiple blood products, vasopressor support, and insertion of a bakri balloon. Placental examination revealed velamentous cord insertion with an accessory lobe consistent with vasa previa. The neonate, delivered with low APGAR scores, required intubation and NICU admission but recovered successfully. Both mother and infant were discharged in stable condition, with favorable outcomes on follow-up. This case underscores the critical importance of early recognition, timely intervention, and multidisciplinary management in vasa previa to prevent catastrophic maternal and fetal morbidity and mortality.